Rapid Bromination Study of Nucleobase-Uracil in Aqueous Medium by Hydrodynamic Voltammetry - Bashir, Willayat; Borkar, V.T.; Dangat, V.T. (Asian Journal of Chemistry, 2016)
The kinetics and mechanism of the rapid bromination of the nucleobase uracil, by molecular bromine in aqueous medium at pH 7 has been studied employing hydrodynamic voltammetry, NMR and FTIR. The formation of the mono-bromo derivative is found to be a second order rapid reaction. The rate constant, energy of activation and frequency factor for the reaction have been determined and a probable mechanism for the reaction has been proposed.